How Start-up Ecosystem in Greece is Recovering from the Effects of the COVID-19 Pandemic - Vasilopoulos, Athanasios; Tsitsakis, Christos (KnE Social Sciences, 2023)
It is well known that the recent global pandemic crisis of 2020, despite the healthrelated problems that it caused, also unstabilized the economies around the globe. That situation led to many business closures, unemployment, extra government funding support for businesses, and many other protective reforms that were necessary in order to restart the economy. However, in Greece, even though this health crisis was rapidly affecting the economy and businesses, reports showed that during the pandemic, start-up businesses seemed to be adapting and handling the new situation quite well. Reports, also indicated, that the quick recovery from the start-up ecosystem, was mainly because there were good opportunities for the most innovative start-ups to further expand their operations and bring innovative solutions to handling the pandemic situation. Furthermore, the government, the universities, and some organizations helped the start-ups to further expand through special health and digital hackathons, dedicated seminars, business accelerators, devoted online support platforms for start-ups, and many more. Therefore, the objective of this short paper is to examine, through the latest literature, studies, and reports, how the Greek start-up ecosystem is recovering and expanding, what were the difficulties of start-up founders, and to find other interesting facts about the start-up ecosystem in Greece, during the first two years of the pandemic. Additionally, we will also try to answer questions that will help us in understanding the current situation. Some of these questions include the difficulties that entrepreneurs had in that period and lastly, if the Greek Government was able to help, through various initiatives, the start-up ecosystem during Covid-19. Keywords: start-ups, Covid-19, Greece